Laser‐Evoked Potentials in Fibromyalgia: The Influence of Greater Occipital Nerve Stimulation on Cerebral Pain Processing. Issue 5 (21st May 2015) - Plazier, Mark; Ost, Jan; Snijders, Erwin; Gilbers, Martijn; Vancamp, Tim; De Ridder, Dirk; Vanneste, Sven
<x xml:space="preserve">Abstract</x> Objective Fibromyalgia causes widespread musculo‐skeletal pain in the four quadrants of the body. Greater occipital nerve stimulation has recently shown beneficial effects in fibromyalgia patients on pain, fatigue, and mood disorders. Laser‐evoked potentials (LEPs) are used for research to understand the pathophysiological mechanisms of pain and to evaluate the effects of pain treatment. In fibromyalgia patients, LEPs tend to have a higher N2 amplitude, a tendency to shorter latencies, and patients have a lower pain threshold. Greater occipital nerve stimulation might exert a modulation of the medial pain pathways processing the affective motivational components of pain (unpleasantness) as well as the descending pain inhibitory pathways (reducing pain), both of which are contributing to the N2P2 peak. Materials and Methods To test this hypothesis, the authors performed LEPs in a group of fibromyalgia patients with and without greater occipital nerve stimulation. Results Occipital nerve stimulation does not alter the amplitudes of the LEP recordings, although a significant difference in latencies can be seen. More specifically, latencies of the N2P2 increased in the condition after stimulation, and especially at the Pz electrode. Conclusion Our results suggest Occipital Nerve Stimulation (ONS) induces a modification of the balance between antinociceptive pain inhibitory pathways and pain‐provoking pathways.